Dendritic Cell Vaccination is Effective Against H3.3G34R Mutant Glioblastoma in a Novel Syngeneic Genetically Engineered Mouse Model. (16th November 2020) - Peeters, Sophie; Owens, Geoffrey; Sun, Matthew Z; Lee, Alexander; Kienzler, Jenny C; Orpilla, Joey; Contreras, Erick; Treger, Janet; Odesa, Silvia; Everson, Richard G; Becher, Oren; Holland, Eric C; et al.
Abstract: INTRODUCTION: The two main subtypes of pediatric glioblastoma (GBM) are marked by highly conserved somatic H3-3A gene mutations. The H3.3G34R/V GBM occurs in children and young adults, typically lobar, and frequently harbor concurrent TP53, ATRX/DAXX, and PDGFRA alterations. H3.3G34 alterations appear to affect K36 residue methylation, which regulates alternative splicing, synchronizing gene regulation through intron retention. We hypothesize that dendritic cell vaccination (DCV) against H3.3G34R GBM stimulates adaptive immunity driven by neoantigen-specific cytotoxic T lymphocytes. METHODS: We developed an H3.3G34R GBM genetically-engineered mouse model by injecting DF-1 avian cells transfected to produce recombinant replication-competent avian sarcoma (RCAS) viruses intraventricular in neonatal C57/Bl-6J transgenic mice harboring homozygous floxed Trp53 and the RCAS virus tv-a receptor under the transcriptional control of the nestin gene promoter. The RCAS viral plasmids used encoded the PDGF receptor a, Cre recombinase, and H3.3G34R cDNAs. Mouse DC's were produced per standard protocol, and pulsed with tumor lysate. Five animals were treated with DC vaccine on days 7 and 22 post-implantation, with six doses of monoclonal PD-1 antibody over 40 days; five animals were untreated. Bioluminescence was used to monitor tumor growth. RESULTS: Three independent glioma lines were generated with G34R mutations confirmed by PCR and DNA sequencing. Tumor generation was 100% in three repeated experiments of five mice each, and mice died or became moribund at 30.5 days on average. All three isogenic cell lines grow as neurospheres in serum free media with supplemental FGF, EGF, and PDGFA/B. Preliminary analyses indicate that gene expression profiles and H3K36me3 landscapes show mild heterogeneity among the three RCAS/tv-a-derived cell lines. Bioluminescence shows three complete responses in the five treated mice, with one mouse in the treated group dying unexpectedly without significant tumor burden. Kaplan-Meier survival analysis suggests a significant survival benefit with treatment. Characterization of the adaptive immune response is ongoing. CONCLUSION: We have created a genetically-representative syngeneic immunocompetent murine model of H3.3G34R GBM where DCV is effectively increasing survival.